Assessing adherence to current national guidelines for appropriate albumin use at an academic medical center - Castillo, Angelina M. (Pharm Pract (Granada), 2018)
OBJECTIVE: To assess adherence to current national guidelines for appropriate albumin use at an academic medical center. METHODS: This retrospective chart review of 150 randomly selected patients prescribed and administered at least one dose of albumin was conducted in an urban academic medical center to evaluate the adherence of albumin orders to current national guidelines. Inclusion criteria consisted of discharged patients at least 18-years-old admitted to the intensive care unit or medical/surgical unit from September 1, 2015 to August 31, 2016. The primary outcome was the number of patients who inappropriately received albumin based on national guidelines and FDA approved indications. Secondary outcomes included the number of patients who received the incorrect concentration or dose of albumin based on indication, as well as the cost associated with inappropriate albumin prescribing. Descriptive statistics were used to report outcomes. RESULTS: There were 68 instances (45%) where albumin was prescribed inappropriately according to guideline recommendations. Of the 82 instances where albumin was used appropriately, 18 patients received an incorrect dose (22%), and 6 received the inappropriate concentration of albumin (7%). The cost for the 150 patients included in the study associated with inappropriate albumin prescribing was approximately $13,000. CONCLUSIONS: This study identified areas for pharmacist intervention to ensure appropriate albumin utilization, as well as proper dosing for the most frequently incorrectly dosed indications, including hepato-renal syndrome, spontaneous bacterial peritonitis, and paracentesis. This study also identified an unexpected indication with significant inappropriate albumin utilization, perioperative hypotension, which is an area for further intervention to monitor and decrease use.